Original paperClinical and sebumetric evaluation of topical emulsions in the treatment of acne vulgaris - Khan, Barkat Ali; Akhtar, Naveed (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2014)
Introduction: Numerous plant products described in the scientific literature show distinct activities on the skin, such as moisturizing, antioxidant, sunscreen, anti-acne and depigmentation. Aim : The main objective of this study was to compare the effectiveness of emulsion formulations containing plant extracts ( Hippophae rhamnoides and Cassia fistula ) and placebo (without plant extracts) on acne patients. Material and methods: A single-blind, randomized, placebo -controlled, split-face study was designed. Two groups of 25 patients each (aged 18–37 years) with grade I and grade II acne vulgaris received active formulations on the left side of their cheeks and placebo on the right side of their cheeks twice daily for 12 weeks. Prior to the study, signed consent was obtained from each patient. The anti-bacterial activity of the extracts and formulations was tested in vitro . The skin sebum contents of patients were evaluated by the sebumeter® and subjectively using a clinical evaluation before and after treatment of 12 weeks. One way ANOVA and Kruskal-Wallis tests were used in the statistical analysis. Results : A significant (p ≤ 0.05) decrease in the level of sebum contents was observed in both groups who used formulations (F1 and F2) containing the plant extract. The difference between pre- and post-treatment levels of sebum contents was statistically significant (p ≤ 0.05). Formulations containing plant extracts were found effective in the reduction of skin sebum contents (anti-acne effects) sebumetrically as well as clinically when compared to placebo (F3). Conclusions : Formulations with 5% plant extracts could be effective, safe, and well-tolerated topical medications for grade I and grade II acne vulgaris. Key words: sebumeter, acne, Cassia fistula , Hippophae rhamnoides .